Experiences for Geriatric Care from Nursing Students' Knowledge: A Qualitative Approach - Elsa Gil-Mateu; Silvia Reverté-Villarroya; Núria Albacar-Riobóo; Josep Barceló-Prats (MDPI AG, 2024)
(1) Background: Studies have shown that clinical experience has an impact on how students perceive geriatric care. The vulnerability of older people particularly allows students to reflect on and evaluate their learning. In this context, communication between tutors and students is important to guiding a contextualized view of the complexity of clinical situations. The principal objective was to explore the feelings, perceptions, and experiences of nursing students in geriatric care units during their practices. (2) Methods: This is a qualitative study using content analysis where the data collected were analyzed deductively. An intentional sample of 81 nursing degree students enrolled in the subject of clinical practices. During these sessions, a dynamic discussion forum was incorporated. (3) Results: There were 6 forums with a total of 591 participants, with an average of 98.5 per forum. Four categories emerged: humanization, geriatric nurse, aging, and learning. (4) Conclusions: A change of management oriented to the person-centered model would improve the quality in the residences and as well as in the expectations of the students towards geriatric nursing. Changing perspectives could be a way to confront and become aware of the fallacies of care that have been evidenced. This study was not registered.